Energy‐Sharing Economy with Renewable Integration and Management in Communities—a State‐of‐the‐Art Review - Yuekuan Zhou (Advanced Energy & Sustainability Research)
Climate change and extreme weather events impose urgent necessities on distributed energy systems with energy flexibility and resilience to survive the district power supply systems. Compared to centralized energy systems, distributed energy systems show more superiorities in power shifting, fast demand response, regional energy allocations, and so on. However, electrification transformation‐ enabled flexible energy sharing, smart energy integration, and advanced management are still in their infancy stages, with unsolved but urgent issues, like large‐scale energy system planning and optimization, energy trading and pricing mechanisms, so on. In this study, energy‐sharing economy with renewable integration and management in communities has been comprehensively reviewed. The “source–grid–load–storage” framework has been implemented on district energy systems with complex relationships among the energy supply–storage–transmission–distribution chain. Roles of energy sharing, integration, and management on energy system sustainability have been provided. Considering widely installed large‐scale renewable energy systems, planning and optimization platforms and tools are provided to guide the distributed/centralized system planning and accurate capacity sizing. Results showed that, multi‐directional power interactions with electrification in buildings and E‐mobility spatiotemporal energy sharing and smart grids enable high renewable penetration, fast power response, energy supply reliability, etc. Unlike traditional fossil fuel‐based power plants, distributed renewable‐supported energy systems (like BIPVs, electric vehicles, etc.) enable emerging energy sharing, integration, and management for energy flexibility and resilience with fast response and energy survivals. Roles of advanced energy include power shifting, fast demand response, regional energy allocations, and so on. Electricity market liberalization can incentivize multi‐stakeholders’ proactivity and market vitality for distributed renewable energy spatiotemporal microgrids. Dynamic energy pricing for the shared power is dependent on the supply–demand relationship, and cost–benefit allocations among different stakeholders need to be investigated for justice and fairness. To avoid performance over or underestimations, advanced approaches are highly necessary for large‐scale energy system planning and optimization. Research results can pave paths for upcoming studies in urban energy system planning, design, and optimization with high energy efficiency and low carbon emissions through joint collaborations from highly economically incentivized participators.